A comparative study on the influence of monovalent, divalent and trivalent doping on the structural, optical and photoluminescence properties of Zn0.96T0.04O (T: Li+, Ca2+& Gd3+) nanoparticles. Issue 10 (July 2019) - Punia, Khushboo; Lal, Ganesh; Alvi, P.A.; Dolia, Satya Narain; Dalela, S.; Modi, Kunal B.; Kumar, Sudhish
Abstract: Nanoparticles of pure ZnO and monovalent, divalent & trivalent doped Zn0.96 T0.04 O (T: Li +, Ca 2+ & Gd 3+ ) were prepared by the nitrate-citrate based sol-gel method. Powder XRD, TEM and photoluminescence data analysis confirmed single phase formation of pure ZnO, Zn0.96 Li0.04 O, Zn0.96 Ca0.04 O and Zn0.96 Gd0.04 O nanocrystals in the wurtzite type hexagonal lattice with surface and intrinsic crystal defects. UV–Vis–NIR optical absorption measurement demonstrated significant optical light absorption in the visible and UV bands for all the samples. A photo absorption peak below 380 nm is observed in all the four samples. The band gap energies were estimated to be 3.03eV, 2.78eV, 2.90eV and 2.79eV for ZnO, Zn0.96 Li0.04 O, Zn0.96 Ca0.04 O and Zn0.96 Gd0.04 O respectively. Monovalent and trivalent doping in ZnO induces reduction in the band gap energy and increment in the refractive index. 325 nm excited photoluminescence spectrums of pure and doped ZnO samples displayed a peak in the UV region and a broad peak in the visible band. Ca, Li and Gd doping in ZnO leads to red shifting of the UV emission band by substantial decrement in the band-gaps. Deconvoluted PL data analysis attests presence of various types of defects in the ZnO lattice which leads to strong electronic emission in the visible band. Computed values of CCT were found to be below 4000 K in these nanocrystalline samples, which makes them suitable material for the household optoelectronic devices. This study suggests that monovalent (Li + ) doping in ZnO is better choice for tuning the optical and photoluminescence properties for their possible utilization in light harvesting and energy conversion applications.